Reconstructive surgery of the lower eyelid in patients affected by basocelular carcinoma - Bernaldo Canto Vidal; Tania Canto Vigil; Danny González Sánchez; Alain Soto Ugalde (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Foundation: Patients with parpebral lesions caused by basocelular carcinomas, come regularly to the Dermatology, Ophtalmology, and Reconstructive Surgery and Maxillofacial surgery consultations. When the surgical treatment of these lesions is not adequate, there may be sequelae such as palpebral deformations which cause functional and esthetics difficulties. Objective: to describe the results of the Castañón surgical technique modified for repairing the lower eyelid of patients affected by basocelular carcinomas. Methods: a study of case series was used, with patients affected by basocelular carcinomas. They were operated by the technique of total or partial excision of the lower eyelid in triangle form and with immediate reconstruction, in the Hospital Dr. Gustavo Aldereguía Lima. Cienfuegos in the year 2015. Results: from the 15 patients who were operated, 9 were women and sex men, all of white race aged between 60 and 80 years. In all it was used the myocutaneous flap, together with a thin layer of cartilage of the auricular concha. From the 15 patients who were operated only one had a torpid evolution, but in the end the result was satisfactory. Conclusion: the modification to the technique introduced by Castañón has the advantage that it avoids the unnecessary loss of tissue, not having to remove in a rectangular form an extensive lesion. Its effectiveness was evidenced in all the patients.